2022
DOI: 10.1002/advs.202203011
|View full text |Cite
|
Sign up to set email alerts
|

Sculpting Rupture‐Free Nuclear Shapes in Fibrous Environments

Abstract: Cytoskeleton-mediated force transmission regulates nucleus morphology. How nuclei shaping occurs in fibrous in vivo environments remains poorly understood. Here suspended nanofiber networks of precisely tunable (nm-μm) diameters are used to quantify nucleus plasticity in fibrous environments mimicking the natural extracellular matrix. Contrary to the apical cap over the nucleus in cells on 2-dimensional surfaces, the cytoskeleton of cells on fibers displays a uniform actin network caging the nucleus. The role … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…In particular, transcription cofactor YAP will give a response to biomechanical tension along with the stretched direction . YAP nuclear translocation may be related to cytoskeleton parallel stretch, FA kinase activation, and zyxin relocation by anisotropic cell nanomechanics. , Cell nanomechanics has been reported to suppress cell senescence and aging by the inhibition of cGAS-STING signaling due to YAP/TAZ mechanotransduction. , In addition, the nuclear shape is changed by cytoskeleton force to regulate chromatin remodeling and phenotype alternation. Therefore, in this study, the nuclear DNA synthesis level could be regulated by the mechanotransduction from anisotropic YAP signaling and biased cell nanomechanics due to chiral FA formation and heterogeneous cytoskeleton assembly (Figure ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In particular, transcription cofactor YAP will give a response to biomechanical tension along with the stretched direction . YAP nuclear translocation may be related to cytoskeleton parallel stretch, FA kinase activation, and zyxin relocation by anisotropic cell nanomechanics. , Cell nanomechanics has been reported to suppress cell senescence and aging by the inhibition of cGAS-STING signaling due to YAP/TAZ mechanotransduction. , In addition, the nuclear shape is changed by cytoskeleton force to regulate chromatin remodeling and phenotype alternation. Therefore, in this study, the nuclear DNA synthesis level could be regulated by the mechanotransduction from anisotropic YAP signaling and biased cell nanomechanics due to chiral FA formation and heterogeneous cytoskeleton assembly (Figure ).…”
Section: Discussionmentioning
confidence: 84%
“…52 YAP nuclear translocation may be related to cytoskeleton parallel stretch, FA kinase activation, and zyxin relocation by anisotropic cell nanomechanics. 53,54 Cell nanomechanics has been reported to suppress cell senescence and aging by the inhibition of cGAS-STING signaling due to YAP/TAZ mechanotransduction. 55,56 In addition, the nuclear shape is changed by cytoskeleton force to regulate chromatin remodeling and phenotype alternation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…We used suspended nanofibers that mimic the loose interstitial network found in vivo with large and small pore sizes to the extent that cells make contact with only single fibers. 52 We have recently shown that nuclei may lack apicobasal polarity, which causes a uniform distribution of proteins, including lamins, actin, and cytoskeleton, 53 which causes compression of the nuclei from all sides of the nanofiber. Thus, the nuclei of the cells attached to suspended nanofibers show considerable differences from the other in vitro systems with constrained apicobasal polarity, potential reason for the difference in heterochromatin organization and dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike conventional tracked-etched membranes which are flat, the fibrous nature of our nanofiber membrane allows for a 3D environment for cell attachment. 63,64 The interface between the monolayers and the track-etched membrane is clearly visible in the confocal Z-stack image.…”
Section: Nanofiber Co-cultures Of Endothelial Cells With Pericytes En...mentioning
confidence: 99%